2016
DOI: 10.4012/dmj.2016-103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of denture cleaners on the surface roughness and <i>Candida albicans</i> adherence of sealant agent coupled denture base materials

Abstract: This study investigated the effect of denture cleansers on the surface roughness and Candida albicans adherence of surface sealant agent coupled denture base resins. One hundred and twenty specimens were fabricated from 2 polymethyl methacrylate (PMMA) (Meliodent; Acron MC) and 1 polyamide (Deflex) denture base materials, coated with a sealant agent (Palaseal) and divided into 4 groups (n=10) according to overnight cleaning procedures: distilled water (control), 5% sodium hypochlorite (NaOCl) and two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
0
24
0
5
Order By: Relevance
“…C. albicans adhesion to resin materials is promoted by oral environment temperature and the acquired pellicle formed over dentures. Ribeiro et al (37) .Found Candida spp. (65.5%) more than Strep.…”
Section: Discussionmentioning
confidence: 98%
“…C. albicans adhesion to resin materials is promoted by oral environment temperature and the acquired pellicle formed over dentures. Ribeiro et al (37) .Found Candida spp. (65.5%) more than Strep.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, this problem and its potential long-term consequences for patients' health have not yet been studied. The reduction in the number and size of scratches, craters, and other damage that occurs on the surface of materials during abrasion is also important due to the fact that they are potential areas where increased adherence of yeast-like fungi to the surface of materials can occur [21,23,109].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have proved the varied effectiveness of removing microorganisms from the surface of prosthetic materials, for example, by using chlorhexidine gluconate, guanidine solution, peroxides, irradiation microwaves, or buy brushing with toothpaste, but these methods result in the loss of various functional properties, including increased roughness [17][18][19][20][21][22], which can facilitate the recolonization of prosthetic materials [23]. It should be emphasized that there are studies questioning the possibility of fully effective removal of microorganisms from the denture using mechanical or chemical cleaning methods [24], suggesting the possibility of penetration of C. albicans into the interior of acrylic materials [25][26][27] which indicates limited disinfection possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the threshold of R a for denture base material is 0.2 µm. At or above this level, microbial retention and plaque accumulation is expected . Results of this study showed that R a values significantly decreased with nano‐coat and Optiglaze for both acrylic materials resulting in smoother surfaces as these coating agents filled the microdefects on the resin surfaces (Fig ) .…”
Section: Discussionmentioning
confidence: 70%